Alternative Opportunities for Small Farms: Peach and Nectarine Production Review - Ali Sarkhosh; Mercy A. Olmstead; Jeffery G. Williamson; Jose Xavier Chaparro; Juanita Popenoe (EDIS, 2019)
This 4-page document discusses peach and nectarine cultivars released by the University of Florida, and how these cultivars increase the potential for expansion of commercial peach and nectarine acreage throughout different areas of Florida. Written by Ali Sarkhosh, Mercy Olmstead, Jeff Williamson, Jose Chaparro, and Juanita Popenoe and published by the UF/IFAS Horticultural Sciences Department. http://edis.ifas.ufl.edu/ac018